Oracle E-business suite 12 financials cookbook : take the hard work out of your daily interactions with e-business suite financials by using the 50+ recipes from this cookbook /: take the hard work out of your daily interactions with e-business suite financials by using the 50+ recipes from this cookbook. (2011) - Unknown
No abstract available